Squeezing the eggs to grow: The mechanobiology of mammalian folliculogenesis - Biswas, Arikta; Ng, Boon Heng; Prabhakaran, Vinod S/O; Chan, Chii Jou (Frontiers in Cell and Developmental Biology, 2022)
The formation of functional eggs (oocyte) in ovarian follicles is arguably one of the most important events in early mammalian development since the oocytes provide the bulk genetic and cytoplasmic materials for successful reproduction. While past studies have identified many genes that are critical to normal ovarian development and function, recent studies have highlighted the role of mechanical force in shaping folliculogenesis. In this Review, we discuss the underlying mechanobiological principles and the force-generating cellular and extracellular structures that control the various stages of follicle development. We also highlight emerging techniques that allow for quantification of mechanical interactions and follicular dynamics during development, and propose new questions for future studies in the field. We hope this review will provide a timely and useful framework for future understanding of mechano-signalling pathways in reproductive biology and diseases.